Cutaneous Melioidosis Presenting as a Red Nasal Plaque: A Case Report - Huang S; Santanirand P; Chairanaicharoen S; Rattananukrom T (Infection and Drug Resistance, 2025)
Sarocha Huang,1 Pitak Santanirand,2 Suwichak Chairanaicharoen,2 Teerapong Rattananukrom1 1Division of Dermatology, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Clinical Pathology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Teerapong Rattananukrom, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +662-201-1141, Fax +662-201-1211, Email teerpongrattananukrom@gmail.comBackground: Melioidosis, caused by Burkholderia pseudomallei, is endemic to tropical regions. Cutaneous forms, often presenting as non-healing ulcers, are rare and may mimic other skin diseases. Recognizing risk factors is key to prompt diagnosis and treatment.Case Presentation: We report the case of a 51-year-old female with a 2-month history of chronic erythematous plaques on her nose. Aerobic tissue culture confirmed the diagnosis of primary cutaneous melioidosis by identifying B. pseudomallei. There was no evidence of systemic involvement, and blood culture results were negative. The patient was successfully treated with oral sulfamethoxazole-trimethoprim monotherapy. After three months of treatment, the lesion resolved completely, leaving an atrophic scar. At the eight-month follow-up, there was no evidence of recurrence.Conclusion: This case illustrates an atypical presentation of cutaneous melioidosis without systemic involvement, which was effectively treated with oral sulfamethoxazole-trimethoprim monotherapy. A comprehensive evaluation to exclude dissemination is critical for ensuring successful treatment outcomes.Keywords: cutaneous melioidosis, nasal plaque, oral therapy, sulfamethoxazole-trimethoprim